Immunosuppressive Treatment for Myocarditis in the Pediatric Population: A Meta-Analysis - He, Bing; Li, Xiaoou; Li, Dan (Frontiers in Pediatrics, 2019)
The use of immunosuppressants in the treatment of myocarditis in children remains controversial. The aim of this meta-analysis is to summarize the current empirical evidence for immunosuppressive treatment for myocarditis in the pediatric population. We searched the Pubmed, MEDLINE and EMBASE for articles to identify studies analyzing the efficiency of immunosuppressive treatment in the pediatric population. Pooled estimates were generated using fixed or random-effect models. Heterogeneity within studies was assessed using Cochran's Q and I2 statistics. Funnel plots and Begg's rank correlation method were constructed to evaluate publication bias. Sensitivity analyses were also conducted to evaluate the potential sources of heterogeneity. After a detailed screening of 159 studies, six separate studies were identified, with 181 patients in the immunosuppressive treatment group and 199 in the conventional treatment group. The immunosuppressive treatment group showed a significant improvement in left ventricular ejection fraction (LVEF)[mean difference 1.10, 95% CI :0.41, 1.79] and significantly decreased left ventricular end diastolic dimension (LVEDD)[mean difference -0.77mm, 95% CI :-1.35 to -0.20mm] when compared to the conventional treatment group. Furthermore, the risk of death and heart transplant in conventional treatment was significantly higher than immunosuppressive treatment group (RR:4.74; 95%CI:2.69, 8.35). No significant heterogeneity across the studies was observed. There was no evidence of publication bias when assessed by Begg's test. Conclusions: There may be a possible benefit, in the short term, to the addition of immunosuppressive therapy in the management of myocarditis in the pediaatric population. However, further prospective investigation is warranted to the validate this finding.Children with myocarditis seem to benefit from immunosuppressive therapy. Immunosuppressive treatment of acute myocarditis in the pediatric population is associated with improved recovery of left ventricular function and with a tendency to better survival.